Visualizing spikes in source-space: Rapid and efficient evaluation of magnetoencephalography. Issue 2 (February 2016) - Beniczky, Sándor; Duez, Lene; Scherg, Michael; Hansen, Peter Orm; Tankisi, Hatice; Sidenius, Per; Sabers, Anne; Pinborg, Lars Hageman; Uldall, Peter; Fuglsang-Frederiksen, Anders
Highlights: MEG signals can be reconstructed in source-space and reviewed in a source-montage corresponding to 29 brain-regions. The accuracy of this method was tested in a prospective, blinded study. Epileptiform MEG discharges were accurately detected in source-space, and the analysis-time was significantly shortened. Abstract: Objective: Reviewing magnetoencephalography (MEG) recordings is time-consuming: signals from the 306 MEG-sensors are typically reviewed divided into six arrays of 51 sensors each, thus browsing each recording six times in order to evaluate all signals. A novel method of reconstructing the MEG signals in source-space was developed using a source-montage of 29 brain-regions and two spatial components to remove magnetocardiographic (MKG) artefacts. Our objective was to evaluate the accuracy of reviewing MEG in source-space. Methods: In 60 consecutive patients with epilepsy, we prospectively evaluated the accuracy of reviewing the MEG signals in source-space as compared to the classical method of reviewing them in sensor-space. Results: All 46 spike-clusters identified in sensor-space were also identified in source-space. Two additional spike-clusters were identified in source-space. As 29 source-channels can be easily displayed simultaneously, MEG recordings had to be browsed only once. Yet, this yielded a global coverage of the recorded signals and enhanced detectability of epileptiform discharges because MKG-artefacts were suppressed and did not impede evaluation in source-space. Conclusions: Our results show that reviewing MEG recordings in source-space is accurate and much more rapid than the classical method of reviewing in sensor-space. Significance: This novel method facilitates the clinical use of MEG.